CCNA 200-301 official cert guide library - Odom, Wendell; Gooley, Jason; Hucaby, Dave (Official cert guide library, 2025)
CCNA 200-301 Official Cert Guide Library is a comprehensive review and practice package for the latest CCNA exam and is the only self-study resource approved by Cisco. The two books contained in this package, CCNA 200-301 Official Cert Guide, Volume 1 and CCNA 200-301 Official Cert Guide, Volume 2, present complete reviews and a challenging and realistic preparation experience. The books have been fully updated to refresh the content for the latest CCNA exam topics and to enhance certain key topics that are critical for exam success. Best-selling author Wendell Odom shares preparation hints and test-taking tips, helping you identify areas of weakness and improve both your conceptual knowledge and hands-on skills.